Case report: Time response of plasma clozapine concentrations on cessation of heavy smoking - Qi, Lingyan; Ma, Botao; Fan, Hongzhen; Qi, Siyuan; Yang, Fude; An, Huimei (Frontiers in Pharmacology, 2024)
Smoking cessation in patients treated with clozapine might lead to elevated plasma concentrations and severe side effects. This case report investigated the trajectory of clozapine plasma concentrations over time after smoking cessation in a Chinese inpatient with schizophrenia. This case report delineates the temporal response of plasma clozapine concentrations and dose-corrected clozapine plasma concentrations in a 33-year-old inpatient with schizophrenia who had a substantial smoking history and ceased smoking abruptly during dose titration. This case report presents a sudden increase in plasma clozapine concentrations and dose-corrected plasma clozapine concentrations after smoking cessation, followed by a rapid decline in dose-corrected plasma clozapine concentrations during the initial 2 weeks and a return to pre-cessation levels approximately 1 month later. The findings suggest that clinicians and pharmacists should adjust clozapine dosage in accordance with changes in smoking status, taking into consideration the temporal effects. Post-smoking cessation adjustments to clozapine dosage should be coupled with therapeutic drug monitoring, especially for patients with heavy smoking habits. Moreover, the advice of the clinical pharmacist should be considered in complex cases to ensure safe use of clozapine.